Rhetorical Structure of Conclusion Chapters in Bachelor TEFL Thesis Written by Indonesian Writers - Amaliah, Ayu; Amin Dalimunte, Ahmad (International Journal of Language Teaching and Education, 2024)
The main purpose of this study is to conduct an in-depth analysis of the rhetorical structure of the conclusion sections in Teaching English as a Foreign Language (TEFL) undergraduate theses written by Indonesian authors. The study aims to explore the moves and steps used in the conclusion section, identifying patterns in the rhetorical structure. This study adopts a qualitative research methodology, The use of a genre analysis emphasis broadens the area of the investigation and makes it easier to recognize and understand the recurrent rhetorical devices and conventions that authors use. Based on the results of the analysis that has been conducted thoroughly on 10 theses. We found that Move 4 (Deduction from the research) is the dominant move with a total of 18 occurrences (38.29%). It is followed by Move 1 (Introducing the conclusion chapter) and Move 2 (Summarizing the research) with 10 occurrences and a percentage of 21.28%. The last is followed by Move 3 (Evaluating the research) with 9 occurrences and a percentage of 19.15%.